Edukasi Kesehatan Metode Jigsaw Dalam Meningkatkan Pengetahuan Pencegahan Gastritis Mahasiswa - Edy Supardi; Sulasri; Reski Fitriani Herman (Poltekkes Kemenkes Yogyakarta, 2025)
Background: Gastritis is a health problem and a digestive tract problem that is most often found in everyday life. Adolescents tend to have a range of gastritis due to unhealthy lifestyles, so prevention efforts are needed, one of which is health education. Jigsaw method is one of the effective and popular educational methods that can be applied to improve knowledge. Objective: to determine the effect of health education with the jigsaw method on knowledge of gastritis prevention in students of Pelamonia Institute of Health Sciences. Methods: This study used a quantitative method, Quasi Experiment one group test design, involving 30 participants of IIK Pelamonia students of ARS study program as a research sample, knowledge was measured using a 13 question questionnaire about gastritis prevention. Results: Wilcoxon test analysis obtained a p value = 0.000, indicating a significant increase in knowledge about gastritis prevention after being educated using the jigsaw method. Conclusion: There is an effect of health education with the jigsaw method on knowledge of gastritis prevention in Pelamonia IIK students, so the use of the collaborative Jigsaw method can be used by nurses as an effective health education method, especially in adolescence.